PERANAN MAJELIS DZIKIR WA SHOLAWAT AR-RAUDAH DALAM HUBUNGAN SOSIAL DI KELURAHAN SIDOREJO KECAMATAN MEDAN TEMBUNG - Assaukhan, Ilham; Susanti, Neila; Jailani, Muhammad (CV. Kalimasada Group, 2024)
This study discusses the role of Majelis Dzikir Wa Sholawat Ar-Raudah in social relations in Kelurahan Sidorejo, Medan Tembung District, Medan City. The general public usually views majelis dzikir from two sides, some who support it and some who see it as heretical. To obtain data, the method used is descriptive quantitative with writings that are described based on the results of observations, interviewus and documentation. The results obtained are that the role of the Majelis Dzikir Wa Sholawat Ar-Raudah is to carry out routine recitations, da'wah, blessed fridays, help orphans and the poor and become a place for learning islamic values ​​and teachings. The community views the dzikir assembly as a community that benefits the community and also considers it to deviate from islamic teachings.